The men's wellbeing project: promoting the well-being and mental health of men. Issue 2 (17th April 2020) - Abotsie, Gabriel; Kingerlee, Roger; Fisk, Andrew; Watts, Sam; Cooke, Rachel; Woodley, Luke; Collins, Dawn; Teague, Bonnie
Abstract : Purpose: Comparatively, men have poorer physical and mental health outcomes than women, with a significantly higher suicide rate. Contributory factors are thought to be social and biological, leading to reduced access to health-care services. The study aims to develop and implement community-based support to increase awareness of and access to men's mental health support networks and groups. Design/methodology/approach: The project involved three key work-packages discussed in this paper: raising awareness of men's mental health needs in health care, educational and community settings; collaboration between National Health Services (NHS) and non-NHS health-care support organisations to build multi-sector partnership working; and developing a supported sports-based community intervention aimed at men living with mental health conditions. The acceptability and feasibility of these work-packages were pragmatically evaluated through mixed-methods surveys and qualitative content analysis. Findings: Overall, both community events and sports groups successfully engaged men living with mental health problems. Organisations interested in men's mental health are continuing to engage in a partnership initiative. Community events were well-attended and received positive feedback, particularly regarding the educative and real-life experiences approach promoted in the events. The sports intervention is feasible and well-accepted by participants, who described feeling supported with their physical and mental health needs, with increased mental well-being reported. Research limitations/implications: The main limitations of this project are that the authors only evaluated a football group rather than all work areas. The project collected outcomes relating to participants' demographics and qualitative reflections of participating in the football group along with a retrospective survey of perceived benefits, but the project did not undertake a pre- and post-comparison of well-being outcomes owing to low completion of these measures. Future work could focus on collecting more pre- and post-measures related to well-being, recovery and inclusion and compare these with men not involved in the football groups or public events. Practical implications: This paper discusses the development and feasibility of setting up community-based men's mental health support networks, involving public events, partnership working and targeted-sports interventions. All initiatives were well-received and successfully attended by men living with mental health conditions. Evaluation of the programme revealed the value placed on education about mental health and the role that community sports interventions may play in men's mental health care. Social implications: This project has demonstrated three different ways of supporting men's mental health needs in the community. Community public events were held to raise awareness of men's mental health needs and issues were well-attended and highlighted the need for health promotion and education in this area across all the communities. The men's football group demonstrated the feasibility of moving mental health support out into a non-clinical and more community arena in a way that men engaged effectively. Finally, the creation of MensNet has bought together disparate multi-sector organisations successfully to lead public health mechanisms to support men's mental health needs. Originality/value: This paper describes a new multi-disciplined approach to supporting health-seeking challenges among men, in particular, how partnership working across NHS and non-NHS sectors can successfully support an identified public health need pragmatically using existing services and organisations.